Upgrading technology in Central and Eastern European economies - Slavo Radosevic (IZA World of Labor, 2017)
The future growth of Central and Eastern Europe (CEE) depends on upgrading technology, exporting and coupling domestic technology efforts while improving their position in global value chains. Current policies in the region are not geared to these tasks, despite the availability of huge financial opportunities in the form of EU structural funds. Existing policies are overly focused on research and development (R&D) and neglect sources of productivity growth, such as management practices, skills, quality, and engineering. The challenge is how to design industrial and innovation policies so that they promote modernization and drive structural change.
Keywords: O1; O3; O52; P2; 330; technology upgrading; productivity; R&D and innovation; Central and Eastern Europe; EU